Analisis Kritis Madrasah Nizamiyah, serta Pengaruhnya terhadap Perkembangan Pendidikan Islam dan Ortodoksi Sunni - Damayanti, Nur Yeka; Zalnur, Muhammad; Masyhudi, Fauza (TSAQOFAH, 2024)
Madrasah Nizhamiyah is an educational institution founded in 457-459 H/1065 AD (IV Century) by Nizham al-Mulk from the Seljuq Dynasty. Nizhamiyah Madrasah is the first madrasah to appear in the history of Islamic education in the form of primary to tertiary educational institutions managed by the government. Nizham al-Mulk's madrasah is called Nizhamiyah and is famous throughout the world, of which the most famous and most important madrasah is Nizhamiyah in Baghdad (apart from the Balkh, Naisabur, Jarat, Ashfahan, Basrah, Marw, Maulus madrasah, etc.). The Nizhamiyah Madrasah can be compared to today's faculties or universities, considering that the teachers were well-known great scholars. The method used in this research is a qualitative method with a library research type of research. In this discussion, the author focuses on deepening the concept of Madrasah Nizamiyah education under the auspices of the Saljuk Dynasty, as well as the concept of education which is widely referred to in the development of Islamic education in the future.